Pengaruh risiko audit, materialitas, prosedur review dan kontrol kualitas, dan komitmen profesional terhadap prematur sign off (studi empiris pada kantor akuntan publik di pekanbaru dan padang) - A, Al-azhar; ', Trinaldi; ', Kamaliah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The study aimed to examine the effect of audit risk, materiality, review procedures and quality control and auditor’s professional commitment that can affect the premature sign off audit procedures.The sample of this research are 51 auditors. Data were collected through a survey to auditors in KAP Pekanbaru and Padang area by using personally administrated questionnaires. Writer tested the quality of data that included validity test and reliability test, normality test, asumsi klasik test, and use the hypothesis by means of multiple regression analysis test, t test,determintion koefficient test, and f test with program software SPSS.The results ofthis study found that audit risk, materiality, review procedures and quality control and auditor’s professional commitment variables have a effect on premature sign off.Keywords : premature sign-off, audit risk, review procedures and quality control,materiality, and professional commitment